2020
DOI: 10.1039/c9ra10701k
|View full text |Cite
|
Sign up to set email alerts
|

A flexible polyelectrolyte-based gel polymer electrolyte for high-performance all-solid-state supercapacitor application

Abstract: A simple polymerization process assisted with UV light for preparing a novel flexible polyelectrolyte-based gel polymer electrolyte (PGPE) is reported. Due to the existence of charged groups in the polyelectrolyte matrix, the PGPE exhibits favorable mechanical strength and excellent ionic conductivity (66.8 mS cm À1 at 25 C). In addition, the all-solid-state supercapacitor fabricated with a PGPE membrane and activated carbon electrodes shows outstanding electrochemical performance. The specific capacitance of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 43 publications
(23 citation statements)
references
References 44 publications
1
22
0
Order By: Relevance
“…6c and d , it is observed that the deformation of the PDPA SC is more significant than that of PGPE SC, suggesting that it cannot maintain high-efficiency ion transmission at the high scan rate. The results are in agreement with the findings of Yan et al , 42 who put forward the charge transport resistance of PDPA SC is enhanced with the increase of the scan rates, so it behaves inferior capacitance characteristic, while the PGPE SC exhibits a typical double-layer capacitance feature. It proves that the addition of the charged groups in PGPE powerfully influences its electrochemical properties.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…6c and d , it is observed that the deformation of the PDPA SC is more significant than that of PGPE SC, suggesting that it cannot maintain high-efficiency ion transmission at the high scan rate. The results are in agreement with the findings of Yan et al , 42 who put forward the charge transport resistance of PDPA SC is enhanced with the increase of the scan rates, so it behaves inferior capacitance characteristic, while the PGPE SC exhibits a typical double-layer capacitance feature. It proves that the addition of the charged groups in PGPE powerfully influences its electrochemical properties.…”
Section: Resultssupporting
confidence: 92%
“…Stalgren et al 29 report two similar monomer with charged groups, one is used in the following work to prepare PGPE. Yan et al 42 develop a system of poly(C 3 (Br)DMAEMA- co -PEGMA) for all-solid-state supercapacitors, which exhibits high ionic conductivity of 66.8 mS cm −1 (25 °C) and excellent mechanical strength. When it is fabricated in the supercapacitor, the electrochemical properties of the device are outstanding.…”
Section: Introductionmentioning
confidence: 99%
“…Ionic conductivity is the most signicant parameter for studying the electrochemical performance of electrolyte membrane. [29][30][31][32][33][34] The bulk resistance (R b ) of the PHL GPE was measured by AC impedance spectrometer, and the conductivity was calculated according to the literature, 35,36 Fig. 2b shows the R b at different temperature from 20 C to 60 C. Obviously, the value of R b becomes smaller with the increasing temperature corresponding to the increasing ionic conductivity.…”
Section: Characterization Of Phl Gpementioning
confidence: 99%
“…Polymer electrolyte has attracted extensive attention which is widely employed in rechargeable lithium ion batteries (RLIBs), super capacitors, and solar cells, etc [1][2][3]. For the few decades, the Li + ion movement is considered and enhanced in conducting performance between anode and cathode by researchers.…”
Section: Introductionmentioning
confidence: 99%